PEMANFAATAN HIDROPONIK AJB SEBAGAI MEDIA BUDIDAYA TANAMAN SELADA (Lactuca sativa L) DI PEKARANGAN RUMAH - Aqhsal, Muhammad (Universitas Mataram, 2023)
The AJB hydroponic system is a type of hydroponics found by managers from Mataram who use a substrate or planting medium in the form of sand. Hydroponics generally allows plant roots to sink in water or nutrient solution, but this can cause the roots of planted plants to decay because they are always in water. In the AJB hydroponic system, the roots of the lettuce plant will not be inundated directly because the water will mix with the sand substrate as the planting medium and the water itself will stagnate under the pot to the limit of the holes in the AJB hydroponic pot. The nutrients used in this system are a mixture of nutrients a and b or AB mix which is given through a pipe in the middle of the pot. This is so that the distribution of nutrients from the middle can be spread evenly. The pipe in the middle also has a hole at a height close to the surface of the soil so that the nutrients provided can reach and stimulate the roots to grow to the bottom where the nutrients are stagnant. In this study, the aspect observed was the growth in height of lettuce leaves/day which was calculated manually using a ruler by providing 1 liter of nutrients per each pot at the beginning and providing nutrients once every 3 days thereafter with a volume of 0.28 liters/each pot. The results of this study were an average growth of 0.286 cm/day for all samples or lettuce seedlings from pot 1 to pot 7.